2022
DOI: 10.3390/ani12162116
|View full text |Cite
|
Sign up to set email alerts
|

Blood Trace Element Status in Camels: A Review

Abstract: Trace minerals play an important role in animal health and productivity. They are involved also in many physiological activities, and their deficiency causes a variety of pathological problems and metabolic defects, reducing consequently the animal productivity. The demand for animal products in semi-arid areas is rapidly increasing, and the supply is still below the required level, partially due to low animal productivity. Camels (Camelus dromedarius and Camelus bactrianus) are considered one of the main sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 120 publications
(174 reference statements)
1
7
0
Order By: Relevance
“…Both trace element deficiency and toxicity were reported to affect the camels’ reproductive and productive efficiency, as well as different aspects of their metabolism and growth. Therefore, assessing the status of trace elements in camels is an important step toward improving the health and productivity of camels ( Abdelrahman et al ., 2022 ). Among these elements, cobalt plays an important role as it is utilized by rumen microflora for synthesizing vitamin B 12 resulting in chronic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Both trace element deficiency and toxicity were reported to affect the camels’ reproductive and productive efficiency, as well as different aspects of their metabolism and growth. Therefore, assessing the status of trace elements in camels is an important step toward improving the health and productivity of camels ( Abdelrahman et al ., 2022 ). Among these elements, cobalt plays an important role as it is utilized by rumen microflora for synthesizing vitamin B 12 resulting in chronic anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Trace mineral elements are essential nutrients for the growth and development of ruminants. Cu is present in various proteins and enzymes, and maintaining an appropriate concentration of Cu is essential for effectively carrying out its physiological, catalytic, and regulatory functions [ 22 ]. Dietary Cu deficiency and supplementation did not significantly alter liver weight, which indicated that Cu status in grazing sheep does not affect liver weight variation.…”
Section: Discussionmentioning
confidence: 99%
“…Periods of undernutrition for copper and zinc have been reported for camel metabolism [ 52 ]. Nutritional factors are believed to control copper status in camel rather than physiology [ 53 ]. The authors report a significant effect of copper supplements in the form of copper sulfate salt.…”
Section: Discussionmentioning
confidence: 99%
“…The authors report a significant effect of copper supplements in the form of copper sulfate salt. Iron deficiency has not been reported in animals grazing in natural conditions [ 53 ]. The formation and excretion of chalcopyrite due to active sulfate reduction in the camel gut can be an overlooked cause of iron and copper deficiency.…”
Section: Discussionmentioning
confidence: 99%